ChemInform Abstract: La3BaSi5N9O2:Ce3+ — A Yellow Phosphor with an Unprecedented Tetrahedra Network Structure Investigated by Combination of Electron Microscopy and Synchrotron X‐Ray Diffraction. Issue 39 (September 2015) - Durach, Dajana; Neudert, Lukas; Schmidt, Peter J.; Oeckler, Oliver; Schnick, Wolfgang
Abstract Agglomerates of a few μm of the yellow phosphor La3BaSi5N9O2:Ce3+ are obtained by heating a mixture of LaF3, La(NH2)3, BaH2, Si(NH)2, and CeF3 in a radio frequency furnace under N2 (1600 °C, 10 h; cooling to 900 °C within 44 h).